Postnatal growth and weight gain in term and near-term infants with severe neonatal hypoglycemia: A comparison between offspring of diabetic and non-diabetic mothers: Growth of infants who have severe neonatal hypoglycemia - Soliman, Ashraf T; Alaaraj, Nada; De Sanctis, Vincenzo; Alyafei , Fawzia; Hamed, Noor; Ahmed, shayma; Ali, Hamdy; Alnaimi, Fatima; Itani, Maya; Okab, Bassant (Acta Biomedica Atenei Parmensis, 2024)
Objective: This study aimed to evaluate postnatal growth patterns in infants with neonatal hypoglycemia, comparing infants of diabetic mothers (IDM) with infants of non-diabetic mothers (INDM) from birth to 3 years of age. Methods: We retrospectively analyzed the growth data of 79 IDM and 51 INDM infants who were treated for severe neonatal hypoglycemia at a single center. Anthropometric measurements, including weight-for-age Z score (WAZ), length-for-age Z score (LAZ), and weight-for-length Z score (WLZ), were collected at birth and at several intervals up to 36 months. Results: IDM were born at a higher gestational age and with better growth indices than INDM. During the first year, IDM had a progressive increase in WAZ, which stabilized thereafter, while INDM presented a significant catch-up in WAZ and LAZ, particularly in the first 18 months. After 2 months, IDM maintained higher WLZ scores than INDM. By 36 months, IDM had significantly higher WAZ and WLZ, suggesting a tendency towards increased weight relative to length. Conclusion: The growth patterns of infants with neonatal hypoglycemia are influenced by maternal diabetes status. While IDMs are at risk for increased adiposity, both groups show resilience in growth, underscoring the need for ongoing monitoring to support their growth needs